Outside in - Bradbury, Jennifer (Jennifer A.) (Atheneum Books for Young Readers, 2017)
A street boy named Ram lives off scraps of food, learns from scraps of conversations he overhears, and only has scraps of memories from his caregiver who is long gone. When he meets an artist named Nek, Ram learns the beauty that can come from scraps as he sees Nek's incredible sculptures composed of bits and pieces of metal, broken glass, other junk.